From Mexico to Beijing: "Women in Development" Twenty Five Years On - Koczberski, Gina (1996)
During the past twenty five years the Women in Development (WID)approach has become an increasingly important issue in the literature on Third World development. WID issues and related activities have now been incorporated into the aid practice of most development agencies. This paper critically analyses the diverse and conflicting ideologies that have emerged in the WID literature since the early seventies.